Flow behaviour assessment of Smokey SAM rocket prototype - Abdullah, Nur Azam; Ismail, Nor Izzuddin; Ismail, Izham Izzat; Azami, Muhammad Hanafi; Nordin, Norhuda Hidayah; Sukindar, Nor Aiman; Abidin, Zulkifli Zainal; Abu Bakar, Ahmad Joahari; Dani, Noriza (Semarak Ilmu Publishing, 2021)
This paper presents an aerodynamic assessment on the "Smokey Sam Prototype (TRL-6) Start (X)". Initially, the rocket prototype was designed using OpenRocket open source software, where all of the user's design requirements and objectives are considered. The TRL-6 Smokey Sam Star (X) is expected to fly within 400 m with the operating Mach 0.2, as comparable to US GTR-18A. This research evaluates the aerodynamics performance of the design Smokey Sam prototype rocket using a computational fluid dynamics (CFD) approach. For instance, the CFD study assessed the flight performance and stability once launched, such as lift coefficient, drag coefficient and pitching moment. This research employs K-omega (k-ω) model to express the turbulent properties of the flow. The actual pressure distribution was compared with the conventional rocket material's exact pressure distribution to inspect the best rocket material to sustain the best strength to weight ratio at high-speed trajectory operation. Several observations were made into the modelling process, such as surrounding velocity and pressure. It is found that the flight is in stable mode since the obtained pitching moments are almost zero at all assessed speeds.